History and material culture : - Harvey, Karen (The Routledge guides to using historical sources, 2009)
Harvey opens up the discussion on sources to those beyond the 'traditional' textual ones, and into the material realm. Through 12 chapters different historians look at a variety of material sources from around the world and across centuries to assess how such sources can be used to study history.